Sanksi Hukum Terhadap Pelanggaran Kode Etik Anggota Kepolisian Yang Menyalahgunakan Narkoba - Dudik Djaja Sidarta; Nur Handayati; Heru Ulin Nuha (CV. Ulil Albab Corp, 2026)
This study aims to analyze law enforcement against police officers who abuse narcotics and the application of criminal sanctions and professional code of ethics for such violations. The research method used is normative juridical legal research with a statutory approach and literature study. The results show that police officers proven to have abused narcotics can be subject to criminal sanctions under Law Number 35 of 2009 concerning Narcotics as well as sanctions based on the Police Professional Code of Ethics. However, in practice, the enforcement of the code of ethics has not been fully effective due to several obstacles in the implementation of sanctions and internal supervision mechanisms. Therefore, stricter and more transparent law enforcement is required to maintain professionalism and public trust in the police institution.